Antimicrobial resistance gene detection in beneficial and pathogenic food related bacteria - van Hoek, A.H.A.M. (Utrecht University, 2009)
Although, the discovery of antibiotics has revolutionised the treatment of infections, the growing phenomenon of bacterial resistance, among others due to the use and abuse of antimicrobial agents, is now threatening to take us back to a pre-antibiotic era. Continuously, microorganisms subtly change their genetic and molecular makeup which helps them to escape the threat caused by the frequent application of antibiotics. After the discovery of antibiotic resistant bacteria phenotypic susceptibility tests have become an essential component of infectious disease management. However, improved knowledge of the genetic backbone of the numerous resistance mechanisms has resulted in the development of various molecular tools, like for example PCR tests. The aim of this thesis was the construction of versatile molecular tools to screen for the presence of a large set of antibiotic resistance (AR) genes in the food related microorganism, Salmonella, Lactic Acid Bacteria (LAB) and Bifidobacterium. It describes the development of a glass slide oligonucleotide microarray in combination with a random primed genomic DNA labelling for the detection of multiple AR gene targets. The microarray currently represents over 430 AR genes through a total of 223 oligonucleotides which comprise determinants encoding resistance to the antibiotic classes; aminoglycoside, beta-lactam, chloramphenicol, MLS, sulfonamide, tetracycline, trimethoprim, and vancomycin. This microarray platform was used to screen a large set of Salmonella isolates belonging to over 25 different serovars for the presence of AR determinants. The generated hybridization data were consistent to the general findings concerning antibiotic resistance in Salmonella. In addition, within the EU project called “ACE-ART” the microarray was applied to analyze numerous sensitive and resistant LAB and bifidobacteria isolates for the possible presence of AR genes. Research was focused on the most frequently identified resistances in the genera studied; erythromycin and tetracycline. The most commonly identified AR gene was tet(W), encoding for a tetracycline ribosomal protection protein. Moreover, tet(M) and tet(S) were also frequently characterized, like the erythromycin resistance determinant erm(B). However, some AR genes were atypical for LAB and bifidobacteria. For example, the phenomenon of mosaic tetracycline resistance genes, identified in Bifidobacterium thermophilum and Lactobacillus johnsonii was described for the first time. In addition, the erythromycin- and clindamycin resistance determinant erm(X) as a part of a Tn5432-like transposon is also a novel result for Bifidobacterium animalis subsp. animalis and Bifidobacterium thermophilum. The transposonal location of this AR gene excludes these isolates from being used as probiotics. The thesis also introduces a novel microarray platform using ArrayTubes for the detection of 42 AR genes and related elements as well as mutation based resistance. The platform includes a ligation detection reaction of padlock probes, removal of non-ligated probes, PCR amplification, and hybridization to a customized 1.5-ml ArrayTube. It was used to screen several Salmonella Paratyphi B d-tartrate positive isolates. The identification of putative AR determinants in phenotypically susceptible isolates suggest to not only determine the resistance phenotype but to also include molecular methods like the microarray platforms developed which have been proven to be functional tools for the screening of multiple AR genes.
Keywords: SDG 3 - Good Health and Well-being